Emergence and evolution of social networks through exploration of the Adjacent Possible space - Enrico Ubaldi (Nature Portfolio, 2021)
Understanding how social interactions between individuals shape the large-scale properties of social networks is key to understanding our society. Here, the authors revisit the Adjacent Possible paradigm to describe the evolution of social networks as a social space exploration process, presenting a simple model that reproduces several empirical features common to diverse real-world social networks.